PENGOLAHAN BAHAN PUSTAKA MELALUI KEGIATAN KLASIFIKASI DI PERPUSTAKAAN WALI NAGARI PARAMBAHAN - Intan Khairatun Nisa; Sri Wahyuni (Jurnal Informasi, Perpustakaan, dan Kearsipan (JIPKA), 2023)
This research will focus on addressing issues in the processing of library materials and developing recommendations to improve the effectiveness and efficiency of processing through appropriate classification activities. Among the processes involved in processing library materials are the selection of materials, determination of subjects, classification of materials, inventorying of materials, cataloging, providing call numbers on the spine of books, and shelving. Therefore, processed library materials can be arranged on bookshelves or known as 'selving'. The purpose of this study is to improve the quality of library services and user satisfaction at the Parambahan Subdistrict Office Library. It also aims to organize library materials at the Parambahan Subdistrict Office Library more neatly so that the information can be utilized by the surrounding community to enhance their knowledge. The results of this study are expected to provide information and input for library managers and stakeholders to improve the processing of library materials in a better and structured manner at the library.Keywords: Processing Of Library Materials, Classification of Library Materials